Leaf appearance in cowpea: effects of temperature and photoperiod - Craufurd, Peter Q.; Subedi, M.; Summerfield, R.J. (Wiley, 1997)
Leaf appearance in crop plants is an important process involved in canopy development. The environmental control of leaf appearance has not been studied in cowpea [Vigna unguiculata (L.) Walp.]. This study was conducted to determine whether photoperiod has any effect on the rate of leaf appearance (RLA) and to determine the phyllochron and its base temperature in cowpea. Five genotypes from W. Africa were sown on nine occasions between 1990 and 1992 at Kano, Nigeria, (12°03′N). Plants were grown in pots under short (9.7–10.8 h d−1), natural (12.3–13.5 h d−1), and long (13.5–14.4 h d−1) day lengths and at mean daily temperatures of between 20.9 and 29.8°C. Eight genotypes, including the five genotypes grown in Nigeria, were also grown at seven mean temperatures ranging from 15.4 to 33.7°C in controlled environment glasshouses during 1994 in the UK. Leaf number on the main shoot was recorded every 2 to 3 d during the course of the experiments. No significant effects (P > 0.05) of photoperiod on RLA were detected in any genotype. Temperature significantly (P < 0.001) affected RLA in all genotypes. The relationship between RLA and mean temperature was similar in experiments in Nigeria and controlled environments. A comparison of the combined Nigerianand controlled environment data sets revealed significant (P < 0.01) differences between genotypes in the intercept but not in the slope of the relationship between RLA and mean temperature. The phyliochron, expressed as thermal time (0) per leaf, was therefore the same in all genotypes, 42°C d, above a base temperature that varied from 7 to 12°C. These values of the phyllochron and its base temperature are similar to those reported for other tropical legumes.